Pencatatan Transaksi Pajak Pertambahan Nilai Kegiatan Membangun Sendiri - Marsono Marsono (Universitas Pamulang, 2022)
Self-building activities (SBA) are objects of value-added tax (VAT) that have special provisions which are different from the object of VAT with general provisions. The method of recording SBA transactions should also be different from recording VAT transactions with general provisions. Errors in recording these transactions can result in errors in fulfilling tax obligations which will result in tax sanctions. This study aims to determine the extent to which the financial accounting and tax accounting literature discusses the recording of SBA and examines its compliance with applicable regulations. The study was conducted by reviewing 15 tax accounting kinds of literature and 10 financial accounting kinds of literature circulating in Indonesia. Based on the results of the study, there are three kinds of literature that include the recording of SBA. However, the explanation in the literature still allows for misinterpretation which can lead to tax sanctions. This study concludes that SBA transactions will be more appropriate if they are recorded in the SBA VAT Payable account rather than the Output VAT/VAT Payable account. This method will provide accurate and clear information about the existence of SBA VAT obligations and the payment period so that the entity can make appropriate decisions.